Studies toward the total synthesis of carba analogue of motif C OF M. TB cell wall AG complex - Gurjar, Mukund K.; Reddy, Challa Nageswar; Kalkote, Uttam R.; Chorghade, Mukund S. (Heterocycles, 2009)
Herein we describe the synthesis of the carba analogue of motif C of arabinogalactan complex present in M tuberculosis cell wall. Pd(0) catalyzed allylic alkylation and Fraser-Reid's glycosidation are the two key reactions that were employed for the synthesis of central glycosyl accepter unit and the glycosylation respectively.
Keywords: Allylic Alkylation; desymmetrization; Fraser-Reid's Glycosidation; M. Tb Ag Complex; Mycobacterium tuberculosis